An Examination of how Pricing Strategy Affects Performance of Oil Marketing Companies in Kenya - William, Kagwima Justus; Joyce, Gakobo (Journal of Marketing and Communication, 2020)
Pricing continues to remain popular as a critical aspect that determines the performance of firms across the globe. However, the extent of influence on performance is contingent upon the level of price sensitivity of a product under consideration. The oil marketing companies in Kenya are facing challenges such as reduced profit margins, inadequate infrastructure, increased competition with the entrance of small independent dealers, price caps and lowering quality standards and these as a result forces the big oil marketers out of the continent for they shift the attention to productive activities and lucrative exploration. Performance in the aforementioned aspects can be investigated from the viewpoint of competitive strategies such as positioning strategies, differentiation strategies, focus strategies and pricing strategies. This study sought to investigate the effect of pricing strategy on the performance of oil marketing companies in Kenya. A descriptive research design was used in this study. The five main oil marketers in Kenya were the target population. The companies were selected since they have the highest market share. The study used qualitative and quantitative techniques in analysing the data. Statistical Package for Social Science (SPSS) software was used to generate descriptive and inferential statistics which were interpreted using mean, standard deviation, percentages, frequencies and coefficients. The study revealed that there is a statistically significant relationship between pricing strategy and the performance of oil marketing companies in Kenya (p=0.02; p<0.05). It was recommended that oil companies should frequently analyse their cost structures to ensure that they work towards reducing their operational costs by putting in place effective cost structures. Keywords: Pricing, Strategy, Marketing, oil, Performance, Kenya